The Three Hundred project: the gas disruption of infalling objects in cluster environments - Mostoghiu, Robert (2021)
We analyse the gas content evolution of infalling haloes in cluster environments from THE THREE HUNDRED project, a collection of 324 numerically modelled galaxy clusters. The haloes in our sample were selected within 5R₂₀₀ of the main cluster halo at z = 0 and have total halo mass M₂₀₀ ≥ 10¹¹h⁻¹M⊙. We track their main progenitors and study their gas evolution since their crossing into the infall region, which we define as 1-4R₂₀₀. Studying the radial trends of our populations using both the full phase space information and a line-of-sight projection, we confirm the Arthur et al. (2019) result and identify a characteristic radius around 1.7R₂₀₀ in 3D and at R₂₀₀ in projection at which infalling haloes lose nearly all of the gas prior their infall. Splitting the trends by subhalo status we show that subhaloes residing in group-mass and low-mass host haloes in the infall region follow similar radial gas-loss trends as their hosts, whereas subhaloes of cluster-mass host haloes are stripped of their gas much further out. Our results show that infalling objects suffer significant gaseous disruption that correlates with time-since-infall, cluster-centric distance and host mass, and that the gaseous disruption they experience is a combination of subhalo pre-processing and object gas depletion at a radius which behaves like an accretion shock.